Estimating the impact of currency unions on trade using a dynamic gravity framework - Douglas L. Campbell (University of California, Department of Economics, 2011)
Does leaving a currency union reduce international trade? This paper reexamines time series estimates of currency unions on trade from a historical perspective using a dynamic gravity equation and by conducting in-depth case studies of currency union breakups. The early large estimates are sensitive to dynamic specifications, and were driven by omitted variables, as many breakups were caused by warfare, communist takeovers, coup d'etats and other major geopolitical events. The methodology has general applicability for the use of gravity equations in policy analysis, and yields an imprecise point estimate of currency unions on trade close to one percent.
Keywords: F15; F33; F54; 330; currency unions; trade; dynamic gravity; decolonization